International Handbook of Teacher Education Volume 2 - Loughran, John; Hamilton, Mary Lynn (Springer Nature Singapore : Imprint: Springer, 2016)
The International Handbooks of Teacher Education cover major issues in the field through chapters that offer detailed literature reviews, designed to help readers to understand the history, issues and research developments across those topics most relevant to the field of teacher education from an international perspective. This volume is divided into two sections: Teacher educators; and, students of teaching. The first examines teacher educators, their role, and the way that role influences the nature of teaching about teaching. In turn, the second explores who students of teaching are, and how that influences the relationship between teaching and learning about teaching.